Claim Procedure Analysis Health BPJS In Hospital - Ida Sugiarti Sugiarti (Indonesian Journal of Health Information Management, 2021)
The membership administration procedure factor, the medical resume factor, the diagnosis codification factor and the action codification factor are still obstacles so that they are returned by the BPJS Health verifier. The purpose of the study was to determine the BPJS Health claim procedure at the hospital. Literature research or literature study and qualitative approach. Based on a review of 15 (fifteen) journals, it was found that there are still obstacles in the BPJS Health claim procedure so that the file is returned to the BPJS verifier. As in the case of membership administration procedures, medical resume factors, diagnosis codification factors, and action codification factors. which causes BPJS health files to be returned, namely the absence of Standard Operating Procedures which regulates the factors regarding the collection of documents for BPJS patient registration requirements. Components of author authentication and audit records are not appropriate because there is no signature of medical personnel and there are still empty parts. And the writing of the diagnosis is not specific so that the codification is not accurate and the coder on memorization does not refer to ICD-10 or only sees ICD-10 volume 3 without looking at Referring to volume 1.